Policy on the Right to Education of Refugees in Indonesia and Australia - Ni Luh Gede Astariyani; I Nyoman Prabu Buana Rumiartha; Ni Ketut Ardani; Thomas John Kenevan (Universitas Negeri Semarang, 2023)
Upholding human rights in the context of education is manifested in the form of the right to education. Realizing this right requires equal distribution of education which means the widest possible educational opportunity for everyone, including fulfilling children's rights to education for refugees or asylum seekers. Based on data from the United Nations High Commissioner for Refugees (UNHCR) in 2021, there are 13,459 refugees in Indonesia, of whom it is estimated that around 27% are child refugees and 114 children of whom come alone or are separated from their families. This research article will discuss the role of the Indonesian state in providing educational rights to children of refugees from other countries or children of asylum seekers as well as international arrangements related to the education rights of children of asylum seekers in transit countries. This study uses normative juridical research methods, through international regulatory approaches and conceptual approaches, in this case studying and analyzing material and legal issues based on international regulations and concepts related to the study of human rights from the perspective of the educational rights of asylum seeker for refugee especially child refugee.